POTENSI KERAGAMAN IKAN DI WADUK KEDUNG OMBO SEBAGAI PENYEDIA KEBUTUHAN PANGAN BERKELANJUTAN - Eko Purnomo; Syifara Chika (Jurnal Biogenerasi, 2022)
The program to build food security can be applied to several aspect such as food safety, food availability, affordability, and food distribution. The program is carried out so that humans can manage natural resources for the availability of food needs in a sustainable manner. One of the most important foods is fish. Fish contains high protein, omega 3 fatty acids, and other nutritional. The purpose of this study was to determine the potential of fish diversity in the Kedung Ombo reservoir as a provider of sustainable food needs. The research method uses survey and literature review. Based on the results of the literature study, it was found that there were 13 types of fish and came from 7 families. The fish species include parrot fish (Oreochromis niloticus), tilapia fish (Oreochromis mossambicus), Catfish (Pangasius sutchi), tawes fish (Barbodes gonionatus) and betutu fish (Oxyeleotris marmorata). In fish farming activities, one of them must be carried out properly, one of which is by paying attention to the concept of inland public waters in a sustainable manner so that its easy for the community to meet their food needs